Effect Of Resistance Running Training To Develop Power And Kinetic Shooting Accuracy In Youth Football Players - Haider Nafel Resen (Journal Sport Science Indonesia, 2026)
This study aims to develop resistance running training for young football players and to identify effect of resistance running training on developing power and kinetic shooting accuracy in young football players. The researcher used experimental method group pre-test/post-test approach, as this method allows for accurate measurement of effect of the independent variable on studied sample. Community and sample consisted of young players from clubs in Al-Nu'maniyah district participating in governorate league, number of players is 72 distributed among 3 clubs, each club has 24 players, these clubs are Al-Shaheed, Al-Nu’maniyah, Al-Wafaa. The researcher selected sample using simple random lottery, sample consisted of 24 players from Al-Nu'maniyah Club, then excluded two goalkeepers, two injured players, and 6 players for pilot study. Final number of players in sample was 14 who represented experimental group, representing 19.4% of total population. After presenting and discussing the results, the researcher reached several conclusions, the most important of which are resistance running training contributed positively and effectively to developing power in young football players, training methods used helped improve efficiency of neuromuscular system and increase speed of motor response in players. Results also showed that exercises similar to real playing conditions help transfer training effect to skill performance more effectively. The researcher recommends necessity of adopting resistance running training within training programs for young football players due to its positive impact on developing power and shooting accuracy from a moving position, and to benefit from results of current study in preparing training curricula for football clubs and schools for youth category.